Epidemiological trends of female breast and gynecologic cancers in adolescents and young adults in China from 1990 to 2019: Results from the Global Burden of Disease Study 2019 - Zhao, Yuting; Qiu, Pei; Yan, Lutong; Li, Shouyu; Yang, Zejian; Zhang, Huimin; He, Jianjun; Zhou, Can (Frontiers in Oncology, 2022)
Background Research on the incidence, mortality, and disability-adjusted life years (DALYs) of female breast and gynecologic cancers (FeBGCs) and the relevant risk factors for adolescents and young adults (AYAs) are valuable for policy-making in China. We aimed to estimate the incidence, deaths, and DALYs and predict epidemiological trends of FeBGCs among AYAs in China between 1990 and 2019. Methods Data from the 2019 Global Burden of Disease (GBD) study between 1990 and 2019 in 195 countries and territories were retrieved. Data about the number of FeBGC incident cases, deaths, DALYs, age-standardized rates (ASRs), and estimated annual percentage changes (EAPCs) were extracted. A comparative risk assessment framework was performed to estimate the risk factors attributable to breast cancer deaths and DALYs, and autoregressive integrated moving average (ARIMA) models were fitted for time-series analysis to predict female cancer morbidity and mortality among Chinese AYAs until 2030. Results In 2019, there are 61,038 incidence cases, 8,944 deaths, and 529,380 DALYs of FeBGCs among the AYAs in China, respectively. The estimated annual percentage change (EAPC) values were positive scores (>0) in ASIRs and negative scores (<0) in ASMR and ASDR. Furthermore, in 2030, the incidence rate of FeBGCs would grow to 30.49 per 100,000 in China, while the mortality rate would maintain a steady state. Of the deaths and DALYs, diet high in red meat was the greatest contributor to breast cancer, while a high body mass index (BMI) was the greatest contributor to cervical, ovarian, and uterine cancers. Conclusion The increasing Chinese FeBGC burden is mainly observed in AYAs and non-red meat diet, and the control of body weight could reduce FeBGC burden in China.